Outsourcing, occupational restructuring, and employee well-being: is there a silver lining? - Böckerman, Petri; Maliranta, Mika (Bonn, 2013)
"This paper examines the relationship between outsourcing and various aspects of employee well-being by devoting special attention to the role of occupational restructuring as a conveying mechanism. Using linked employer-employee data, we find that offshoring involves job destruction, especially when the destination is a low-wage country. In such circumstances, staying employees' job satisfaction is reduced. However, the relationship between outsourcing and employee well-being is not entirely negative. Our evidence also shows that offshoring to high-wage countries stimulates the vertical mobility of employees in affected firms in a manner that improves perceived well-being, particularly in terms of better prospects for promotion."